Study of the Prevalence of Subclinical Ketosis in the Central Region of Syria (Journal of Hama University, 2024)
This study was conducted to determine the prevalence of subclinical mastitis in cows in the central region of Syria, based on the California CMT test. The effect of subclinical mastitis on milk pH and somatic cell counts in milk was also studied.Where this study was conducted on 800 samples of milk taken from 200 heads of dairy cows in the period between 5/6/2021 to 16/2/2022, as milk samples were collected from cows in different areas of the countryside of Homs and Hama.The results of the statistical analysis of the study showed a high prevalence of subclinical mastitis disease among cows in the central region, reaching 60%. Compared with uninfected cows (6.61).The results also showed that there was a significant increase at the level (P>0.05) in the number of somatic cells in cows infected with subclinical mastitis, with an average number of (8.07 x 106) compared to the number of uninfected cows (2.25 x 104).This study highlighted the seriousness and impact of subclinical mastitis and the importance of periodic examination of dairy cows.